Antimutagenic and Synergistic Cytotoxic Effect of Cisplatin and Honey Bee Venom on 4T1 Invasive Mammary Carcinoma Cell Line - Faranak Shiassi Arani; Latifeh Karimzadeh; Seyed Mohammad Ghafoori; Mohammad Nabiuni (Advances in Pharmacological Sciences)
Introduction. Honey bee venom (HBV) has various biological activities such as the inhibitory effect on several types of cancer. Cisplatin is an old and potent drug to treat most of the cancers. Our aim in the present study was to determine antimutagenic and cytotoxic effects of HBV on mammary carcinoma, exclusively and in combination with cisplatin. Methods. In this study, 4T1 cell line was cultured in RPMI-1640 with 10% fetal bovine serum (FBS), at 37°C in humidified CO2 incubator. The cell viabilities were examined by the MTT assay. Also, HBV was screened‏ for its antimutagenic activity via the Ames test. The results were assessed by SPSS software version 19 and one-way ANOVA method considering p<0.05 level of significance. Results. The results showed that 6 mg/ml of HBV, 20 μg/ml of cisplatin, and 6 mg/ml HBV with 10 μg/ml cisplatin could induce approximately 50% of 4T1 cell death. The concentration 7 mg/ml of HBV with of 62.76% inhibitory rate showed the highest antimutagenic activity in comparison with other treatment groups. Conclusions. The MTT assay demonstrated that HBV and cisplatin could cause cell death in a dose-dependent manner. The cytotoxic effect of cisplatin also promoted by HBV. Ames test outcomes indicated that HBV could act as a significant mutagenic agent. The antimutagenic activity of HBV was increased considerably in the presence of S9 mix. Therefore, our findings have revealed that HBV can enhance the cytotoxic effect of cisplatin drug and its cancer-preventing effects.